2010
DOI: 10.1111/j.1365-2249.2010.04286.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Parabacteroides distasonis antigens attenuates experimental murine colitis through modulation of immunity and microbiota composition

Abstract: SummaryCommensal bacteria have been shown to modulate the host mucosal immune system. Here, we report that oral treatment of BALB/c mice with components from the commensal, Parabacteroides distasonis, significantly reduces the severity of intestinal inflammation in murine models of acute and chronic colitis induced by dextran sulphate sodium (DSS). The membranous fraction of P. distasonis (mPd) prevented DSS-induced increases in several proinflammatory cytokines, increased mPd-specific serum antibodies and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
262
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(280 citation statements)
references
References 46 publications
15
262
2
1
Order By: Relevance
“…In human biopsies, P. distasonis was significantly more abundant in uninflamed versus inflamed tissue (Zitomersky et al, 2013). Consistent with this observation, oral administration of P. distasonis antigens attenuates intestinal inflammation during colitis in mice (Kverka et al, 2011).…”
Section: Taxonomic Associations With Fungal-induced Cytokine Responsessupporting
confidence: 71%
“…In human biopsies, P. distasonis was significantly more abundant in uninflamed versus inflamed tissue (Zitomersky et al, 2013). Consistent with this observation, oral administration of P. distasonis antigens attenuates intestinal inflammation during colitis in mice (Kverka et al, 2011).…”
Section: Taxonomic Associations With Fungal-induced Cytokine Responsessupporting
confidence: 71%
“…In addition, our result shows a much higher increase of the P. distasonis in ProPre and ProTreat than in control and cisplatin groups (Fig. 3D), suggesting that the intestinal inflammation could be attenuated in the Prohep groups due to the antiinflammatory characteristics of this species (26). Besides the significantly increased species, we also noticed that the major Th17-inducing bacteria, segmented filamentous bacteria (SFB), decreased dramatically in the ProPre and ProTreat groups but remained at a similar level in the control group, suggesting that the proinflammation activities from particular pathogens in the intestine were also suppressed upon probiotics feeding.…”
Section: Probiotics Mediate the Structural And Functional Compositionmentioning
confidence: 62%
“…The relative abundance of Alistipes, a major SCFAs producer in gut (25), decreased in the control group but increased in the ProPre and ProTreat groups by 32% and 29%, respectively. Among other enriched genera in the ProPre group, Oscillibacter and Parabacteroides are associated with T-cell differentiation by enhancing and maintaining the IL-10 producing Treg cells (26,27). One major species of the genus Parabacteroides, Parabacteroides distasonis, has the ability to reduce the intestinal inflammation by inducing the antiinflammatory cytokine IL-10 and suppressing the secretion of inflammatory cytokine IL-17, IL-6, and IFN-γ (26).…”
Section: Probiotics Mediate the Structural And Functional Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…78 Furthermore, we found that this effect could be modulated via the manipulation of the gut microbiota and immunomodulation of the mucosal and the systemic immune response. 79 Thus, the mechanisms of this protective and therapeutic effect should be elucidated more precisely, and this novel approach may be used for the development of a potential vaccine.…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%